2012
DOI: 10.1007/s00345-011-0820-y
|View full text |Cite
|
Sign up to set email alerts
|

Which clinical risk factors determine a pathological urodynamic evaluation in patients with multiple sclerosis? an analysis of 100 prospective cases

Abstract: The urodynamic investigation at hand showed urinary tract dysfunction in 78 of 100 MS patients with lower urinary tract symptoms (LUTS). The long latency between the occurrence of MS and/or the beginning of LUTS and the first neuro-urological evaluation indicates a deficit in treatment. Beyond national guidelines, all MS patients should at regular intervals be questioned about LUTS and receive urodynamic assessment especially according to the presented risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
6
30
1
2
Order By: Relevance
“…Although Blaivas et al 32 showed that 73% of MS patients without UDS were treated inappropriately, it remains an evaluation tool mainly employed by neurourologists. Wiedemann et al 33 tried to define risk profiling necessitating UDS. EDSS ≥6.5 MS subtypes other than relapsing-remitting and the use of more than one incontinence pad per day were found to increase the likelihood of abnormal UDS findings.…”
Section: Imagingmentioning
confidence: 99%
“…Although Blaivas et al 32 showed that 73% of MS patients without UDS were treated inappropriately, it remains an evaluation tool mainly employed by neurourologists. Wiedemann et al 33 tried to define risk profiling necessitating UDS. EDSS ≥6.5 MS subtypes other than relapsing-remitting and the use of more than one incontinence pad per day were found to increase the likelihood of abnormal UDS findings.…”
Section: Imagingmentioning
confidence: 99%
“…After duplicates removal (n = 100), 147 of 180 screened articles were excluded because they were not related to the neuro-urological follow-up. In all, 23 of 33 full-text articles were included in the quantitative synthesis [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Thus, 10 articles were excluded because they did not bring additional information on the neuro-urological follow-up (six review articles, two case-reports, one animal model, one cross-sectional study) [25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were focused on SCI (13 articles), spinal dysraphism (threee articles), and MS (twoarticles). Main results are presented on Table 1 [9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the test does not have to be used as an initial tool in the evaluation of all MS patients or as part of a routine follow-up. UDS still clearly has a role in MS as it accurately diagnoses the dysfunction that is present [54]. The most common urodynamic finding is NDO, reported in as many as 70 %, followed by DSD, in 25 %.…”
Section: Role Of Urodynamicsmentioning
confidence: 97%